Efecto de dietas artificiales en la crianza de galleria mellonella l. (lepidoptera: pyralidae) - Salas Otiniano, Marco Antonio (2015)
The present research work took to end at Crianza's Laboratory of Insectos Beneficial of the Former Experiment Station Large House of the Empresa Agroindustrial Casa Grande SAC, enter the months of Octubre of the 2014 to Febrero of 2015. The objective of work was to evaluate the effect of artificial diets in Galleria's breeding mellonella the L and determining which one of the diets under consideration enables getting the bigger number from big larvae, in ideal condition, to be used as alternative innkeeper in Paratheresia's production claripalpis Wulp. This insect's breeding came true following techniques you develop for Insectos's technical staff of Crianza's Laboratory Beneficial, with modifications embraced by the author. They collected themselves and Galleria's views selected mellonella the laboratory's L of the modules of breeding and they entered in books for the later planting in the correspondent diets each treatment. The diets prepared on the basis of them dose stipulated for each diet themselves and they distributed themselves at the rate of 350 gr for each treatment, stops at a later time including the quantity of views, according to each treatment. Passed the larvae's harvest accomplished 25 days after planting itself. They evaluated the following variables: Percentage of recuperation and physical and morphologic recovered larvae's characteristics, and cocones's percentage of recuperation of empupamiento. Mellonella determined the effect of the diets and the number of eggs utilized in larvae's breeding of G itself in the present work L.; Utilizing a Complete Design at random with a repair factorial with two factors, Dieta and Número of eggs with 7 levels and 2 two levels respectively, with four repetitions for treatment. Statistical proofs like stockings and confidence intervals in order to determine principal effects and interactions of the factors took effect . Of all of the treatments once 4 with 500 eggs were evaluated, with the diet (T8 ), the best results in relation to the evaluated variables were obtained.